2021
DOI: 10.3390/photonics8040131
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Silicon Photonics for Enabling Next-Generation Space Systems

Abstract: A review of silicon photonics for space applications is presented. The benefits and advantages of size, weight, power, and cost (SWaP-C) metrics inherent to silicon photonics are summarized. Motivation for their use in optical communications systems and microwave photonics is addressed. The current state of our understanding of radiation effects in silicon photonics is included in this discussion. Total-ionizing dose, displacement damage, and single-event transient effects are discussed in detail for germanium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…While the space impact on electronic ICs has been studied for decades, the impact on PICs is a relatively new topic of research and there are still many open questions. 21,22 However, several studies showed promising results in terms of resilience to the space environment. For example, total ionizing dose (TID), which is one of the main radiation effects, does not introduce significant additional losses in InP, 23 Si, 24,25 SiN, 26 a-Si, 26,27 SiC, 28 and SiO 2 29 waveguides.…”
Section: Space Environment Considerationsmentioning
confidence: 99%
“…While the space impact on electronic ICs has been studied for decades, the impact on PICs is a relatively new topic of research and there are still many open questions. 21,22 However, several studies showed promising results in terms of resilience to the space environment. For example, total ionizing dose (TID), which is one of the main radiation effects, does not introduce significant additional losses in InP, 23 Si, 24,25 SiN, 26 a-Si, 26,27 SiC, 28 and SiO 2 29 waveguides.…”
Section: Space Environment Considerationsmentioning
confidence: 99%
“…The growing integration of numerous optical elements or components at a chip-scale level is amplifying the appeal of photonics for space. As these chips advance in complexity and functionality, they are now being used in new space applications, such as integrated photonics for laser space communications, space sensors, and analog and RF applications [12], [13]. Furthermore, combining radio-frequency (RF) and optical communication capabilities has become valuable for EO and telecommunication systems due to reduced launch costs and easier accessibility (Figure 1).…”
Section: Global Photonics Market For Space and Industrymentioning
confidence: 99%
“…InP platforms enable the high-bandwidth lasers, modulators, photodiodes, and optical amplifiers, offering a pathway to optoelectronic monolithic integration and good reliability [212], [213]. SiPh leverages existing complementary metal-oxide-semiconductor (CMOS) process technology, thereby offering a more cost-effective implementation and a more compact footprint [214], [215]. The Si 3 N 4 platform provides very low propagation losses, low fiber coupling loss, enabling filtering and beam shaping applications, at a potentially low cost [216], [217].…”
Section: E Imwp-integrated Microwave Photonicsmentioning
confidence: 99%